SOIL IMPROVEMENT ANALYSIS FOR CONTAINER YARD USING PREFABRICATED VERTICAL DRAINS (PVD) AND PRELOADING: A CASE STUDY OF RECLAIMED LAND IN THE MADURA STRAIT - Muhammad Teja Pribadi Pamungkas; Andhy Romdani; Zakwan Gusnadi; Hery Setiyaji; Daniel Bara Padang Allo (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2026)
This study aims to analyze the effectiveness of the Prefabricated Vertical Drain (PVD) and Preloading methods in accelerating the consolidation process and improving subgrade stability. The analysis was conducted using two-dimensional Finite Element Method (FEM 2D) software. The soil conditions were dominated by clay with varying consistency to the SPT test depth. The simulation results showed that under unimproved conditions, the 90% settlement reached 1,34 m with a consolidation time of approximately ±39 years and landslides occurred on the slope, indicating unstable conditions. After improvement, the main settlement of 1,64 m occurred during a waiting period of 420 days. The remaining settlement during the operational period was 27,84 cm, still below the design limit of 30 cm, with the FK value increasing to 1,617 (FK > 1.3) during the construction period and 1,617 (FK > 1,5) during the operational period. The results show that the combination of PVD and preloading methods effectively accelerates consolidation, controls settlement, and improves the stability of soft soil in container terminal reclamation projects